COMPARATIVE ANALYSIS OF ECONOMIC ORDER QUANTITY AND JUST IN TIME METHODS FOR POLYESTER INVENTORY CONTROL - Iksan Fadillah; Afif Fawa Idul Fata; Priyo Ari Wibowo (KOMITMEN: Jurnal Ilmiah Manajemen, 2026)
Polyester is the core raw material for the production process at PT Indo-Rama Technologies Complex, and inconsistent inventory control caused overstock conditions and rising holding costs at the Raw Material Godown (RMG) Department. This study aimed to determine the optimal order quantity and the minimum Total Inventory Cost (TIC) of polyester raw material by comparing the company's existing policy with the Economic Order Quantity (EOQ) and Just in Time (JIT) methods. A quantitative descriptive approach was applied using five months of inventory and demand data, with ordering cost and holding cost as the main variables. The results showed that the existing company policy generated an order quantity of 6,124 units with a TIC of Rp11,190,975.05. The EOQ method produced an optimal order quantity of 17,751 units with two order frequencies and a TIC of Rp6,900,459, saving about 38.3% compared to the existing policy. The JIT method mathematically produced the lowest TIC (Rp3,983,981.86) but required an unrealistic order frequency of 133 times in five months. Considering operational feasibility, supplier lead time, and import administration constraints, the EOQ method was concluded to be the most efficient and applicable inventory control policy for polyester raw material.